Under Milk Wood; A Play for Voices - Thomas, Dylan; Edited by Davies, Walford; Maud, Ralph; Introduction by Davies, Walford (London Phoenix, 2000)
In 1951, two years before his death, Dylan Thomas wrote of his plan to complete a radio play, 'an impression for voices, an entertainment out of the darkness, of the town I live in, and to write it simply and warmly and comically with lots of movement and varieties of moods, so that, at many levels...you come to know the town as an inhabitant of it'. The work was UNDER MILK WOOD - an orchestration of voices, sights and sounds that conjure up the dreams and waking hours of an imagined Welsh seaside village within the cycle of one day. Includes an introduction, notes, selected criticism and chronology of Thomas's life and times.
Include Notes.
A Play for Voices.
Keywords: English drama -- Wales -- Villages -- Play